Aqueous humor metabolomic profiling identifies a distinct signature in pseudoexfoliation syndrome - Zemitis, Arturs; Vanags, Juris; Schiemer, Theresa; Klavins, Kristaps; Laganovska, Guna (Frontiers in Molecular Biosciences, 2025)
PurposePEXS was first described in 1917, yet its etiology still needs clarification. An imbalance between oxidants and antioxidants plays a significant role. PEXS leads to various ocular complications, including increased risk during cataract surgery due to weak zonules, lens dislocation, and reduced visual outcomes. Our study investigates whether metabolomics can provide insights into this ocular pathology.MethodsThe study included 183 patients undergoing cataract surgery at Pauls Stradins Clinical University Hospital. 104 patients did not have PEXS, while 79 were diagnosed with the condition. Intraocular fluid samples from these patients were analyzed using targeted metabolite analysis, performed through HILIC liquid chromatography coupled with mass spectrometry detection.ResultsThe aqueous humor of PEXS patients contains statistically significant higher levels of cystine (p < 0.001), citrulline (p < 0.001), phenylalanine (p = 0.041), tyrosine (p = 0.025), serine (p = 0.030), arginine (p = 0.017), lactic acid (p = 0.055), tryptophan (p = 0.055), and creatinine (p = 0.022). These results suggest a potential link to ferroptosis.ConclusionFerroptosis is a form of programmed cell death characterized by iron-dependent LPO. The inhibition of the antiporter system Xc− leads to increased oxidative stress, suggesting that the changes seen in PEXS could be linked to ferroptosis. Our findings indicate that cysteine synthesis occurs via the transsulfation pathway, attributable to inhibiting the antiporter system Xc−. Treatment of pseudoexfoliation should lower the oxidative stress inside the anterior chamber by reducing the uptake of PUFAs, lower iron levels, and cysteine supplementation.